Business Intellegenge untuk Perencanaan Strategi Pemasaran pada UMKM Sarung dengan Manajemen Dashboard - Wahyu Setianto; Devi Sugianti; Ari Putra Wibowo; Risqiati Risqiati; Arief Soma Darmawan (Universitas Methodist Indonesia, 2025)
MSMEs are the backbone of the national economy, the government is trying to recover the economy after the Covid-19 pandemic by making a new breakthrough with digitalization. Digitalization helps MSMEs to process and analyze data for decision making. The data stored in the company is increasing, so it requires Business Intelligence to make it easier for companies to present information. MSME Abitex experienced problems in planning sales strategies by looking at interest in each city. The stages of research carried out were problem identification, data collection, design, manufacture, testing results. In identifying problems, problems were found in monitoring sales to create sales strategies, in data collection from 2021 to 2023. The number of transactions was 807 sales with 3 types of sarongs, a total of 14 sarongs produced. In designing using a star schema obtained from the sales fact table, time dim, customer dim, goods dim. Business intelligence can display data visualization by grouping by product, customer and by time, and can see interest in products in each city